Functional analysis of a grapevine carotenoid cleavage dioxygenase (VvCCD1) - Lashbrooke, Justin Graham (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Viticulture and Oenology. Wine Biotechnology))--University of Stellenbosch, 2010.